TERT Promoter C228T and C250T Hotspot Mutations Are Absent in BRAF V600E‐Positive Langerhans Cell Histiocytosis - Abdou Malik Da Silva; Zofia Hélias‐Rodzewicz; Irena Ungureanu; Jean‐François Emile (Cancer Medicine)
ABSTRACT Background In various malignancies, the co‐occurrence of BRAF V600E and TERT promoter mutations (C228T and C250T) has been associated with tumor aggressiveness and poor prognosis. However, the presence of these TERT promoter mutations in Langerhans cell histiocytosis (LCH) remains unexplored. Methods We investigated the prevalence of TERT promoter C228T and C250T mutations in 40 formalin‐fixed, paraffin‐embedded (FFPE) LCH samples positive for BRAF V600E. A nested PCR approach followed by Sanger sequencing, complemented by NGS, was used for mutation screening. Results The variant allele frequency (VAF) of BRAF V600E in the analyzed samples ranged from 0.1% to 33.6%, with a median of 17%, and 33 of 40 successfully amplified LCH samples did not harbor TERT C228T or C250T mutations. Conclusion Our findings indicate that LCH BRAF V600E‐positive samples lack the TERT promoter C228T and C250T hotspot mutations. This suggests that TERT promoter mutations may not play a significant role in LCH pathogenesis.